Using synthetic control to assess the impact of light rail transit on neighborhood demographics: A case study of Charlotte’s South End - Renzy, Rory; Artzer, Mary Catherine (Case studies on transport policy, 2025)
•Charlotte’s South End has seen a dramatic revitalization in jobs and housing.•The region’s light rail system may have contributed to this neighborhood change via transit-oriented development (TOD).•A synthetic control approach shows increases in younger and high-income people.•There are also increases in professional workers and decreases in low-income people.•Effects for all outcomes were delayed for a few years after LRT and TOD treatment. Charlotte, North Carolina is one of the fastest growing regions in the country. Its growth in population and industry has led to an increasingly sprawling cityscape, generating urban issues associated with car dependence. To provide transportation alternatives, the regional transit authority opened the LYNX Blue Line in late 2007, the first of two public transit lines that cross the city. Using publicly available Census data and a synthetic control approach, we assess demographic compositional change in South End, a popular “live-work- play” area that has been a focus of transit-oriented development since the Blue Line’s opening. We find that South End experienced an increase in young, high income, and professional services workers, while it also experienced a decrease in low-income workers relative to expectations from non-treated synthetic controls. Results are lagged, suggesting that development surrounding station build-outs played a significant role in driving the observed demographic shifts within the neighborhood. This work helps to understand the step-by-step connections between transit investment, associated residential and commercial development, and demographic change at the neighborhood level.